Synthesis of [18F]-γ-Fluoro-α,β-unsaturated Esters and Ketones via Vinylogous 18F-Fluorination of α-Diazoacetates with [18F]AgF - Thompson, Stephen; Lee, So Jeong; Jackson, Isaac M.; Ichiishi, Naoko; Brooks, Allen F.; Sanford, Melanie S.; Scott, Peter J. H. (Synthesis, 2019)
This communication reports a method for the vinylogous radiofluorination of α-diazoacetates to generate [18F]-γ-fluoro-α,β-unsaturated esters and ketones in moderate to good radiochemical yields. The method uses no-carrier-added [18F]AgF and is compatible with aromatic and non-aromatic substrates and a number of different functional groups. The labeling method is showcased in the synthesis of a fluorinated cholest-5-en-3-one derivative as well as a difluorinated product pertinent to drug discovery.
Keywords: fluorine-18; late-stage fluorination; PET radiochemistry; diazo chemistry; positron emission tomography